Improving students’ achievements on application letter material through differentiated instruction learning - Apriceli, Apriceli (Jurnal EDUCATIO: Jurnal Pendidikan Indonesia, 2023)
Differentiated instruction is a series of learning activities that provide opportunities for students to explore their potential, adapting their interests and learning profiles. Differentiated instruction is an effort conducted by teacher to adapt learning content, learning processes and products that they can produce according to their readiness, interests, talents and learning profile. In this activity, students are expected to be able to be involved in learning activities related to least 3 aspects such as readiness, interests and student profile. Students' ability to learn English at 12 IPA 3 SMAN 1 Batam in the 2023/2024 academic year is relatively low. This is classroom action research which consists of two cycles. It used quantitative research methods in the form of written tests and qualitative research methods using observation sheets and self-reflection sheets. The results are students’ achievement of learning completeness from the initial pre-cycle conditions obtained from 36.36% to 74.25% in cycle I and in cycle II 93.33%.